Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

A new European plant-specific emission inventory of biogenic volatile organic compounds for use in atmospheric transport models - Karl, M; Guenther, A; Koble, R; Leip, A; Seufert, G (BIOGEOSCIENCES, 2009)
We present a new European plant-specific emission inventory for isoprene, monoterpenes, sesquiterpenes and oxygenated VOC (OVOC), on a spatial resolution of 0.089x0.089 degrees, for implementation in atmospheric transport models. The inventory incorporates more accurate data on foliar biomass densities from several litterfall databases that became available in the last years for the main tree species in Europe. A bioclimatic correction factor was introduced to correct the foliar biomass densities of trees and crops for the different plant growth conditions that can be found in Pan-Europe. Long-term seasonal variability of agriculture and forest emissions was taken into account by implementing a new growing season concept. The 2004-2005 averaged annual total biogenic volatile organic compound (BVOC) emissions for the Pan-European domain are estimated to be about 12 Tg with a large contribution from the OVOC class of about 4.5 Tg and from monoterpenes of about 4 Tg. Annual isoprene emissions are found to be about 3.5 Tg, insensitive to the chosen emission algorithm. Emissions of OVOC were found to originate to a large extent from agriculture. Further experiments on crop emissions should be carried out to check the validity of the applied standard emission factors. The new inventory aims at a fully transparent and verifiable aggregation of detailed land use information and at the inclusion of plant-specific emission data. Though plant-specific land use data is available with relatively high accuracy, a lack of experimental biomass densities and emission data on terpenes, sesquiterpenes and oxygenated VOC, in particular for agricultural plants, currently limits the setup of a highly accurate plant-specific emission inventory.
APS
Keywords: Emissions; isoprene; Monoterpenes; VOC

Volatile organic compounds from Italian vegetation and their interaction with ozone. - Calfapietra, Carlo; Fares, Silvano; Loreto, Francesco (Environmental pollution (Barking, Essex : 1987), 2009)
Volatile Organic Compounds (VOCs) emitted from vegetation (particularly isoprenoids) represent an important source of atmospheric hydrocarbons almost double the anthropogenic source. When biogenic VOC mix with NO(x) in the presence of UV radiation, ozone (O(3)) is formed. In Italy, optimal conditions for O(3) formation in terms of VOC/NO(x) ratios and abundance of UV radiation occur for long periods of the year. Moreover, Italian vegetation includes several species that are strong and evergreen isoprenoid emitters, and high temperatures for part of the year further stimulate these temperature-dependent emissions. We review emission of isoprenoids from Italian vegetation, current knowledge on the impact of rising O(3) levels on isoprenoid emission, and evidence showing that isoprenoids can increase both the O(3) flux to the plant and protection against oxidative stress because of their antioxidant functions. This trait not only influences plant tolerance to O(3) but also may substantially alter the flux of O(3) between atmosphere and biosphere.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 19019511
Keywords: antioxidant; isoprene; Monoterpene; Ozone flux; VOC

Elevated atmospheric CO2 causes seasonal changes in carbonyl emissions from Quercus ilex - KREUZWIESER, JÜRGEN; Cojocariu, Cristian; Jüssen, Vera; RENNENBERG, HEINZ (New Phytologist, 2002)
* • The effect of elevated atmospheric CO2 on the carbonyl emissions of leaves from two Mediterranean oak species (Quercus ilex and Q. pubescens) was analyzed under field conditions. * • Physiological and meteorological parameters were determined in parallel with measurements of carbonyl emissions. Gas exchange was quantified in dynamic cuvettes combined with an infrared gas analyzer. * • Acetaldehyde and acetone emissions from leaves of Q. ilex were enhanced by elevated CO2 in the autumn (from 14–40 nmol m−2 min−1 and from 2–8 nmol m−2 min−1, respectively), but not in the summer. No significant effects were found for leaves of Q. pubescens. The effects of CO2 on Q. ilex were mainly a result of decreased emissions by control trees under ambient CO2 concentrations in the autumn; emissions from trees exposed to elevated CO2 remained at a high level. * • Elevated atmospheric CO2 causes autumnal changes in carbonyl emissions from Quercus ilex. These effects suggest that the production of acetaldehyde and acetone depend on developmental factors. It is not yet clear whether the altered carbonyl emissions are a unique feature of Q. ilex.
Keywords: Acetaldehyde; carbonyl emission; Elevated CO2; Quercus ilex; Quercus pubescens; VOC

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC